2020
DOI: 10.1038/s41467-020-15025-1
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT limits immune pathology during viral infections

Abstract: Co-inhibitory pathways have a fundamental function in regulating T cell responses and control the balance between promoting efficient effector functions and restricting immune pathology. The TIGIT pathway has been implicated in promoting T cell dysfunction in chronic viral infection. Importantly, TIGIT signaling is functionally linked to IL-10 expression, which has an effect on both virus control and maintenance of tissue homeostasis. However, whether TIGIT has a function in viral persistence or limiting tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 68 publications
(95 reference statements)
3
42
0
Order By: Relevance
“…However, excessive immune responses to influenza virus can lead cytokine storms, which cause pathological damage to tissues. Immune checkpoints can limit such immune pathology; for example, TIGIT can reduce immune-mediated tissue damage in an IL-10-dependent manner during acute virus infection [81]. The negative regulatory function of T-cells was found to be improved in a mutant mouse with a deletion in the distal cytoplasmic domain of TIM-3.…”
Section: Immune Checkpoints In Influenzamentioning
confidence: 99%
“…However, excessive immune responses to influenza virus can lead cytokine storms, which cause pathological damage to tissues. Immune checkpoints can limit such immune pathology; for example, TIGIT can reduce immune-mediated tissue damage in an IL-10-dependent manner during acute virus infection [81]. The negative regulatory function of T-cells was found to be improved in a mutant mouse with a deletion in the distal cytoplasmic domain of TIM-3.…”
Section: Immune Checkpoints In Influenzamentioning
confidence: 99%
“…Indeed, preclinical studies have found that ARBs, including losartan, can prevent COVID-19 pulmonary injuries, suggesting that ANG II/AT-1R signaling drives the immune defects associated with SARS-CoV-2 (70). Moreover, as the TIGIT pathway has been found to promote immune dysregulation in response to many viral infections, it is likely that SARS-CoV-2 may manipulate this EM to evade detection (10). Indeed, elevated levels of IL-10, a TIGIT-signaling cytokine, have been documented in COVID-19 patients, suggesting that SARS-CoV-2 exploits these proteins to cover its molecular signatures (Figure 4) (94).…”
Section: Excess Ang II Promotes Premature Ec Senescence Along With Dymentioning
confidence: 99%
“…In addition, faulty coagulation, associated with deep venous thrombosis (DVT) and pulmonary embolism (PE), has further complicated the management of this syndrome (7). These prior findings have been replicated in relation to SARS-CoV-2 and seem to precede the development of critical illness, suggesting that defective immunity may play a major role in this disease (8)(9)(10). Indeed, as in avian influenza, the upregulation of NK cell, and CTC exhaustion GRAPHICAL ABSTRACT | The SARS-CoV-2 virus engages the angiotensin-converting enzyme-2 (ACE-2) protein, displacing its physiological ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, at very high antigen doses, T cells revert to Th2 differentiation, potentially due to the susceptibility of Th1 cells to activation induced cell death (AICD) (47,48). AICD of Th1 cells might also contribute to biased Tfh generation at the higher end of TCR signal strength during Clone-13 infection (49,50).…”
Section: Discussionmentioning
confidence: 99%